The crime in mind : criminal responsibility and the Victorian novel - Rodensky, Lisa (Oxford University Press, 2003)
This interdisciplinary study of legal and literary narratives argues that the novel's particular power to represent the interior life of its characters both challenges the law's definitions of criminal responsibility and reaffirms them. By means of connecting major novelists with prominent jurists and legal historians of the era, it offers profound new ways of thinking about the Victorian period.